Longitudinal road profile model generation based on measurement data using mathematical approach - Buhari, Rosnawati (2014)
This study was conducted to produce road profile model based on vertical displacement data from instrument walking profiler and road scanner that could be implemented in long term pavement performance model for predicting the dynamic loading of the vehicles tyre. Road profiles data was supplied by IKRAM Engineering, Malaysia. A vertical distance data from two roads, approximately 0.8 km of new federal road and 5 km of state road were obtained. The International Roughness Index (1RI) was used to classfi types of road based on the IRI classification. The IRI for each sample of road profile was computed using software named ProVal and FOOTWORKs. Road profile generating process was followed the theory Dodds and Robson and also Hardy and Cebon. The process was performed using MATLAB software. After generating road profiles, the calibration between reference and generated road profiles was performed by calculating the corelation coeffrcient value. The correlation coefficient value ranges between -0.7 to -l and 0.7 to I is considered to have a similarity each other. As a results, for federal and state road, several models of road profiles were generated for each sample data. In conclusion, all the road profiles generated will be able to be used as an ahernative road profile in long term pavement performance analysis.